Primary plasma cell leukemia: clinical and laboratory presentation, gene-expression profiling, and clinical outcome with Total Therapy protocols - Usmani, Saad Z (2012)
To determine whether primary plasma cell leukemia (PPCL) remains a high-risk multiple myeloma feature in the context of contemporary therapy and gene expression profiling (GEP), we reviewed records of 1474 patients with myeloma who were enrolled in Total Therapy protocols or treated identically off protocol. 27 patients (1.8%) were classified as having PPCL. As a group, these patients more often had low hemoglobin, high beta-2-microglobulin, high lactate dehydrogenase, low albumin, and cytogenetic abnormalities. Among 866 patients with GEP results, the PPCL group more often had disease that was classified as high risk, and in CD-1 and MF molecular subgroups. Regardless of the therapeutic protocol, patients with PPCL had shorter median overall survival (1.8 years), progression-free survival (0.8 years), and complete response duration (1.3 years) than the remainder whose clinical outcomes had improved markedly with successive protocols. Multivariate analyses of pretreatment parameters showed that PPCL was a highly significant independent adverse feature linked to overall survival, progression-free survival, and complete response duration. In GEP analyses, 203 gene probes distinguished PPCL from non-PPCL; the identified genes were involved the LXR/RXR activation, inositol metabolism, hepatic fibrosis/hepatic stellate-cell activation, and LPS/IL-1-mediated inhibition of RXR function pathways. Different treatment approaches building on these genomic differences may improve the grave outcome of patients with PPCL.